Integrating Technology-Enhanced Language Learning (TELL) into English Language Teaching (ELT) at STAIN Mandailing Natal - Harahap, Sartika Dewi; Lubis, Rica Umrina; Hidayani, Syarifah (Institut Agama Islam Negeri Parepare, 2025)
This study explores the integration of Technology-Enhanced Language Learning (TELL) and its impact on English Language Teaching (ELT). The research addresses the issue of how technology influences students' learning experiences in ELT. The study aims to examine students' perspectives on the use of digital tools in language learning and their effectiveness in enhancing the learning process. A case study approach was employed, with data collected through the interactive platform Mentimeter. Fourteen students from the Tadris Bahasa Inggris Study Program at STAIN Mandailing Natal participated by providing their opinions on the integration of technology in ELT during a presentation session. The analysis reveals that the majority of respondents expressed positive perceptions of technology use in ELT. Students highlighted those various digital tools introduce a new dimension to learning, making the process more engaging and accessible. Key benefits identified include easier access to resources, increased interactivity, and greater flexibility in learning. These findings emphasize the significance of incorporating digital tools into language instruction to enhance the overall learning experience.